The magic of thinking big - Schwartz, David J (Giza, Egypt (3GdedJbi GdKbGajs, 2021)
The Magic of Thinking Big gives you useful methods, not empty promises. Dr. Schwartz presents a carefully designed program for getting the most out of your job, your marriage and family life, and your community. He proves that you don$1 (Bt need to be an intellectual or have innate talent to attain great success and satisfaction$1 (Bbut you do need to learn and understand the habit of thinking and behaving in ways that will get you there. This book gives you those secrets!s
Keywords: Level of Aspiration; Self - Confidence; Success